If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2u + 4(u + -2) = -4 Reorder the terms: -2u + 4(-2 + u) = -4 -2u + (-2 * 4 + u * 4) = -4 -2u + (-8 + 4u) = -4 Reorder the terms: -8 + -2u + 4u = -4 Combine like terms: -2u + 4u = 2u -8 + 2u = -4 Solving -8 + 2u = -4 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2u = -4 + 8 Combine like terms: -8 + 8 = 0 0 + 2u = -4 + 8 2u = -4 + 8 Combine like terms: -4 + 8 = 4 2u = 4 Divide each side by '2'. u = 2 Simplifying u = 2
| 4x(x+2)+11-4=2x+3 | | 12s^4+32s^2-8=0 | | 5(x-5)-6x=-2 | | 7/12*9/2-33/40 | | (2x^2-6x-8)/(x+1) | | 3s^4+8s^2-2=0 | | 7/x+3-5/x-3=3x/x^2-9 | | 14x^2/7x | | -13+6=m-10 | | 6v^2+3v-4=-4v^2 | | 3a^2-14a-5=0 | | 2v^2+3v-4=0 | | -13+6=m-16 | | y=-1*1 | | 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 | | y=-3/4*1+6 | | -0.75*-3/4x+6 | | x^2+5x-37.5=0 | | 96x^2-204x-99=0 | | 450+0.06s=0.06s+900 | | x-43=0 | | 3(6s+12)-10s-6=0 | | 6*4-4y=-24 | | 15c^2-17c-42=0 | | 6x-4*4=-24 | | x^2-x-169=0 | | 13x+10y=20 | | 44x+7=x | | 3(n)+7=46 | | (1/2)x-15=30 |